2010
DOI: 10.1097/mao.0b013e3181c2a0e1
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Vestibular Evoked Myogenic Potentials Via Bone-Conducted Vibrations Applied to Various Midsagittal Cranial Sites

Abstract: The Fpz may be the optimal site for BCV stimulation for screening oVEMPs in reflex magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…The stimulation rate was 5 Hz, with the analysis time for each response of 60 ms, and 30 responses were averaged for each run. Bilateral oVEMPs were recorded simultaneously [Lin et al, 2010].…”
Section: Ovemp Test Using Bcv Modementioning
confidence: 99%
“…The stimulation rate was 5 Hz, with the analysis time for each response of 60 ms, and 30 responses were averaged for each run. Bilateral oVEMPs were recorded simultaneously [Lin et al, 2010].…”
Section: Ovemp Test Using Bcv Modementioning
confidence: 99%
“…The stimulation rate was 5 Hz, with the analysis time for each response of 60 ms, and 30 responses were averaged for each run. Bilateral oVEMPs were recorded simultaneously (13).…”
Section: Ovemp Testmentioning
confidence: 99%
“…On the other hand, Iwasaki et al (2008a) found no difference between oVEMPs produced by head taps to the hairline and inion. In another study (Lin et al 2010), these responses differed in the latency of their first negative peak. The authors explained this finding by the differing conduction velocities of BC sound when stimuli were applied to the anterior sites of the head compared to the inion.…”
Section: Introductionmentioning
confidence: 92%